Factors Influencing Organizational Performance in Hotel Sector of Nepal (Journal of Nepalese Business Studies, 2021)
The present study is designed to identify the factors influencing organizational performance based on native research work carried out through field study. Adopting descriptive cum analytical research design, this study is based on primary data obtained from the hotels located inside the Kathmandu valley of Nepal through the use of a five-point Likert-type questionnaire. With the help of the random sampling technique, 130 employees working in 23 hotels in the position of executive, managerial and officer’s level are taken as sample respondents. Four different variables affecting hotels' performance i.e., qualification, training and experience, administrative efficiency and location are taken as the independent variables and organizational performance as the dependent variable.  Descriptive and inferential statistics have been used in this study. All the variables obtained Cronbach alpha value greater than .65, which shows the consistency on items taken for the study. The correlation analysis showed a strong positive correlation between organization performance and performance factors in the Nepalese hotel sector. Moreover, the regression analysis indicated that qualification of the employee, administrative efficiency of hotel management and training and experience provided to the employee are found strong predictors of organizational performance but the location factor was not found the determinant of organization performance in the Nepalese hotel sector. This study can further expand by adopting other variables affecting organizational performance in the hospitality sectors of Nepal.